Contested cultural heritage religion, nationalism, erasure, and exclusion in a global world - Silverman, Helaine; SpringerLink (Online service). (New York, New York London Springer, 2011)
Cultural heritage is material tangible and intangible that signifies a culture's history or legacy. It has become a venue for contestation, ranging in scale from protesting to violently claimed and destroyed. But who defines what is to be preserved and what is to be erased? As cultural heritage becomes increasingly significant across the world, the number of issues for critical analysis and, hopefully, mediation, arise. The issue stems from various groups: religious, ethnic, national, political, and others come together to claim, appropriate, use, exclude, or erase markers and manifestations of their own and others? cultural heritage as a means for asserting, defending, or denying critical claims to power, land, and legitimacy. Can cultural heritage be well managed and promoted while at the same time kept within parameters so as to diminish contestation? The cases herein rage from Greece, Spain, Egypt, the UK, Syria, Zimbabwe, Italy, the Balkans, Bénin, and Central America
Contested cultural heritage : a selective historiography Helaine Silverman The stratigraphy of forgetting : the Great Mosque of Cordoba and its contested legacy D. Fairchild Ruggles Aestheticized geographies of conflict : the politicization of culture and the culture of politics in Belfast's mural tradition Alexandra Hartnett Blood of our ancestors : cultural heritage management in the Balkans Michael L. Galaty Re-imagining the national past : negotiating the roles of science, religion, and history in contemporary British ghost tourism Michele M. Hanks Collecting and repatriating Egypt's past : toward a new nationalism Salima Ikram National identity interrupted : the mutilation of the Parthenon Marbles and the Greek claim for repatriation Vasiliki Kynourgiopoulou Syrian national museums : regional politics and the imagined community Kari A. Zobler Contestation from the top : Fascism in the realm of culture and Italy's conception of the past Alvaro Higueras Touring the slave route : inaccurate authenticities in Bénin, West Africa Timothy R. Landry Carving the nation : Zimbabwean sculptors and the contested heritage of aesthetics Lance L. Larkin Afterword : El Pilar and Maya cultural heritage : reflections of a cheerful pessimist Anabel Ford
Includes bibliographical references and index
Electronic reproduction.
Keywords: Cultural property; Historic preservation; Cultural policy; Archaeology -- Political aspects; Nationalism